Security posture assessment for Shapadu Corporation Sdn. Bhd / Ediwarman Mohamad Taher - Mohamad Taher, Ediwarman (2013)
Information is the critical asset of any organizations. Data captured, recorded and shared every day is the heartbeat of an organization to secure its relationships with vendors and customers, as well as the foundation for its internal operations and business processes. Having specific, relevant and correct information can make a huge difference to an organization's efficiency as its survival. To protect the information from misuse, abuse and destruction, organizations are willing to spend on technical solutions and comprehensive monitoring tools. However, organizations will still be at risk if they are unable to perform any security assessment of their infrastructure especially on their network, system, application and its infrastructure. The purpose of this study is to identify any vulnerability that may arise in external or internal of Shapadu Corporation Sdn. Bhd's premise. This study also proposes method and technique in order to perform vulnerability assessment and host assessment. The implementation tool has been used in the experimental design which is Nessus scanner. The outcome of this study is a result of the finding, analysis and the recommendation that can be used to rectify the vulnerability and issue in order to ensure ICT infrastructure is secured and to avoid a malevolent individual from exploit vulnerability or execute a denial of service attack to Shapadu Corporation's ICT infrastructure.